Network‐coded diversity protocol for collision recovery in slotted ALOHA networks. (7th November 2013) - Cocco, G.; Alagha, N.; Ibars, C.; Cioni, S.; Corazza, Giovanni; Vanelli‐Coralli, Alessandro; Scalise, Sandro; Niebla, Cristina Párraga; De Gaudenzi, Riccardo; Ginesi, Alberto; Mosquera, Carlos
SUMMARY We propose a collision recovery scheme for symbol‐synchronous slotted ALOHA based on physical layer network coding over extended Galois fields. Information is extracted from colliding bursts allowing to achieve higher maximum throughput with respect to previously proposed collision recovery schemes. An energy efficiency analysis is also performed, and it is shown that by adjusting the transmission probability, high energy efficiency can be achieved. A performance evaluation is carried out using the proposed algorithms, revealing remarkable performance in terms of normalized throughput. Copyright © 2013 John Wiley & Sons, Ltd.